Transforming Primary Science Learning with AI-Based Interactive Multimedia: Impacts on Critical Thinking Skills in Primary Education - Sari, Yunita; Jupriyanto, Jupriyanto; Ismiyanti, Yulina; Amelia, Winda (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to develop AI-based interactive multimedia and evaluate its feasibility and effectiveness in enhancing the critical thinking skills of elementary school students. The research employed a Research and Development (R&D) method using the ADDIE model, consisting of the Analysis, Design, Development, Implementation, and Evaluation phases. The participants were 52 elementary school students. The instruments used in this study included expert validation questionnaires, user response questionnaires, and critical thinking test sheets. Data were analyzed through expert validation analysis, teacher and student practicality response analysis, and critical thinking test analysis of students in the experimental and control groups using the t-test and N-Gain test. The expert validation results showed average scores of 93.7% from material experts, 94.8% from media experts, and 95% from linguists, all categorized as “very valid,” indicating that the AI-based interactive multimedia is highly appropriate for use. The effectiveness test, conducted by comparing pretest and posttest results of 26 control-class students and 26 experimental-class students, revealed that the control class obtained an average pretest score of 58.85 and a posttest score of 75.00, whereas the experimental class obtained 60.05 and 86.08, respectively. The t-test yielded a Sig. (2-tailed) value of 0.000 < 0.05, indicating a significant difference in students’ critical thinking abilities between the experimental and control classes. The N-Gain score of 65 indicated a moderately effective category. In conclusion, the AI-based interactive multimedia developed for science learning content is feasible and effective in improving elementary students’ critical thinking skills.